Scenario analysis for low cost carriers in Singapore. - Koh, Choon Hian. (2008)
The main aim of this study seeks to provide scenarios for the budget airlines in Singapore, which would help industry firms better cope with the dynamic environment. By analysing the external influencing factors, the most likely scenario is painted and implications evaluated.